Wheels4Rent: a web-based vehicle rental and management system with Short Message Service (SMS) notification / Siti Zulaikha Zaidi and Mohd Nizam Osman - Zaidi, Siti Zulaikha; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Wheels4Rent is a web-based vehicle rental and management system integrated with Short Message Service (SMS) notification technology to better manage the operations of a vehicle rental business. This system's evolution has also made it possible for users to browse and book from a wide range of vehicles available online without needing to physically visit any of the rental places. This system incorporates SMS notification technology that helps to notify users about the status of their rental bookings. This system also enables the admin to keep track of the rental records in time and manage all the rental requests systematically. The target users for this system are the local community. The researcher has developed this system based on System Development Life Cycle (SDLC) by using the Waterfall Model as the methodology. The system is developed with PHP and MySQL by using Notepad++ and phpMyAdmin serving as the respective code editors and database management tools. The User Acceptance Testing (UAT) was conducted to evaluate user’s acceptance of the developed system.